(untitled) (Bangladesh Armed Forces Medical Journal, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is one of the largest contributors to global morbidity and mortality from noncommunicable diseases. The chronic nature of the T2DM, coupled with the demands of its management, often leads to significant psychological stress which is known as diabetes-related distress (DRD). DRD encompasses the emotional burden of living with diabetes, fears about long-term complications, and frustrations related to managing the disease. Aim: To find out the determinants of DRD among the T2DM patients attending the outpatient department of Combined Military Hospital (CMH) Rajendropur. Methods: This cross-sectional study was conducted among 223 previously diagnosed T2DM patients from August 2022 to November 2022 attending at the outpatient department (OPD) of CMH Rajendropur. Respondents were selected purposively and data collection was done by face-to-face interview using validated 17-items Diabetes Distress Scale (DDS-17). Results: Among the 223 T2DM patients, 73.1% had no distress, 20.2% had moderate and 6.7% had severe distress with 11.2%, 6.7%, 32.7% and 4% had severe distress in emotional, physician, regimen and interpersonal related distress respectively. Binary logistic regression analysis revealed that having monthly family income <1000-taka (95% CI; 1.042-5.622), performing physical exercise <25 minutes daily (OR 3.200, 95% CI: 1.046 – 9.789) and having dyslipidemia (OR: 3.020, 95% CI: 0.828 – 11.022) were significant predictor for the development of diabetes related distress. Conclusion: Our study revealed that DRD is prevalent in low-income group patients, not having adequate physical exercise and T2DM patient with dyslipidemia. Bangladesh Armed Forces Med J Vol 58 No (1) June 2025, pp 7-16